Éducation Relative À L’environnement En Milieu Scolaire Ivoirien : Réflexion Pour Un Regard Critique - Brou Ahossi Nicolas (European Scientific Journal, ESJ, 2016)
Environmental education uses some means and methods in order to create an environmental consciousness to the population. However, one seems to ignore the different hindrances engendered by the lack of appropriate teaching materials. The weight and influence of society and culture are perceived as potential obstacles. Our work aims at drawing people’s attention on what can be regarded as essential in education in connection with the environment of Côte d’Ivoire such as school environment. In our work, we will focus on the content and the methods of the teachings of this specific domain. In so doing, we will have a glance on primary school boys and their teachers’ behaviors and attitudes. This will help us to see the relationship they establish between “Health and Environment”. The methodology will revolve around the analysis of the content of the teachings and on a qualitative and quantitative study. Primary school boys and their teachers is target population of the survey. At the end of our analysis, it appears that the content of teachings linked to environment is not so explicit. The teaching method is suffering from a lack of explicit didactic and pedagogic materials. From the viewpoint of learns and teachers, we note a paradox between their words and deeds concerning environment. Finally, the link the learners and their teachers establish between Health and Environment let us see some problems of health. We wonder if people are aware of the threats and the social representations of environment in school zone for a sustainable development of our society. This is what can be a logic outcome of work.